Development of oxidation heat of the coal left in the mined-out area of a longwall face: Modelling using the fluent software - Taraba B.; Slovak V.; Michalec Z.; Chura J.; Taufer A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A commercial CFD software program, Fluent, was used to study oxidation processes in the longwall mined-out (gob) area. A three-dimensional model of the gob area with an advancing coal face has been developed. For the model, typical oxidation behavior of a bituminous coal from the Ostrava-Karviná District was incorporated as resulted from laboratory investigations. The longwall gob area was designed on the basis of the actual longwall face district. Detailed measurements in the district then enabled re-verification of the model outputs with actual data in situ. The main attention was paid to modelling the effect of grain size of the coal left in the mined-out area on the oxidation heat and gases evolution. Numerical simulations confirmed the existence of an 'optimal' zone for intense development of the spontaneous heating process in the gob area.